MAPEAMENTO DOS FATORES DE RISCO COM SERVIDORES DO INSTITUTO FEDERAL DE ALAGOAS/REITORIA (Fiep Bulletin - online, 2019)
Concerned about the health and quality of life of teachers and employees that compose the framework, I decided from thisresearch project to plan and organize a research aimed at the employees of the Federal Institute of Alagoas/Câmpus Reitoria. Thisstudy will add value to the question of studying and mapping some health-related risk factors in the Maceió Campus population, whichwill be monitored through metabolic rates, body composition and blood pressure (BP). The present study has as general objective, tostudy and to map some risk factors related to the health of the Federal Institute of Alagoas/Reitoria. The present study will be definedas a quasi-experimental research according to Clarke (1970), cited by Flegner & Dias (1995), because it intends to verify therelationship of human performance under experimental conditions. In this case, map the risk factors with servers of the FederalInstitute of Alagoas/Reitoria. It is hoped that the results that will be presented in this research can contribute positively and fill a gapand emptiness and that from that study, we make the intervention so that the health and quality of life of the federal public servant ofthe Reitoria.
Keywords: Risk; Health and Quality of Life Mapping